PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT.SUMBER ALFARIA TRIJAYA Tbk - Agussalim Rahman,; Umar,; Rizki Khamala Wildaini Caesaria,; Afriyani, (Journal of Innovation Research and Knowledge, 2021)
The purpose of this study was to determine the effect of the current ratio and debt to assets ratio on the return on assets at PT. Sumber Alfaria Trijaya Tbk. The type of data used in this research is quantitative and qualitative data. The data source used in this study is secondary data at 2011-2020. The analytical method used is descriptive quantitative and multiple linear regression to determine the regression coefficient, correlation coefficient, coefficient of determination, t test, F test. The results obtained by the regression equation Y = 0.208 - 0.073X1 - 0.001X2 + e, R value of 0.487 which it means that the variables X1 and X2 and Y have a moderate relationship, the value of R2 is 0.237=23.7% The t-test results for CR are -1.447 and DAR are -0.874, and the F-test results obtained are 1.090. This shows that the current ratio (CR) and debt to assets ratio (DAR) either partially or simultaneously have a negative and insignificant effect on the return on assets (ROA) at PT. Sumber Alfaria Trijaya Tbk.